Optimization Of Business Strategy Through Performance Measurement With KPIS and The Utilization Of Digital Technology In Addressing External And Internal Environments - Havizh, Muhammad; wiansih, Leni; Riandi, Arif; Supratikta, Hadi (Program Pascasarjana Universitas Negeri Makassar, 2025)
This study aims to analyze the optimization of business strategy through performance measurement using Key Performance Indicators (KPIs) and the utilization of digital technology in addressing challenges from both external and internal environments. The rapid development of digital technology and changing market dynamics require companies to continually evaluate and adjust their strategies. KPIs serve as a measurement tool that allows businesses to monitor and analyze their performance in various aspects such as financial, operational, and customer satisfaction. This research examines how the application of digital technology, such as information systems and data analytics, can support more effective and efficient performance measurement processes. Additionally, the study highlights the importance of understanding the company's external and internal conditions, which include market trends, government policies, as well as organizational resources and culture. The findings of this research indicate that the integration of KPIs with digital technology provides significant competitive advantages, enabling companies to be more responsive to challenges and seize available opportunities. Therefore, business strategies based on clear performance measurement and the utilization of digital technology are key to achieving sustainability and optimal business growth.